2009
DOI: 10.1007/s11340-009-9301-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Fatigue Behavior in Nanocrystalline Metals

Abstract: Nanocrystalline metals have been shown to exhibit unique mechanical behavior, including break-down in Hall-Petch behavior, suppression of dislocation-mediated plasticity, induction of grain boundary sliding, and induction of mechanical grain coarsening. Early research on the fatigue behavior of nanocrystalline metals shows evidence of improved fatigue resistance compared to traditional microcrystalline metals. In this review, experimental and modeling observations are used to evaluate aspects of cyclic plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 151 publications
4
104
0
Order By: Relevance
“…However, a survey of the available literature on the fatigue of NC metals reveals that fatigue failure still occurs for NC metals, often with nothing more than a modest improvement in performance over CG metals. [26,27] Perhaps the explanation for the lack of dramatic improvements in fatigue performance is related to the instability of NC grain structures, which are known to evolve even during storage at room temperature. [28] Previous experimental observations of NC grain growth during plastic deformation, [29,30] indentation experiments [31] and as a result of fatigue loading [14,32] warrant serious consideration.…”
Section: Introductionmentioning
confidence: 99%
“…However, a survey of the available literature on the fatigue of NC metals reveals that fatigue failure still occurs for NC metals, often with nothing more than a modest improvement in performance over CG metals. [26,27] Perhaps the explanation for the lack of dramatic improvements in fatigue performance is related to the instability of NC grain structures, which are known to evolve even during storage at room temperature. [28] Previous experimental observations of NC grain growth during plastic deformation, [29,30] indentation experiments [31] and as a result of fatigue loading [14,32] warrant serious consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In many metallic films (e.g. Ni, Cu and Ag) the grains spontaneously coarsen ("self-annealing"), a phenomenon that can also be driven by stress [1][2][3][4][5][6]. Nanocrystalline Ni, for example, has been shown to display a typical power law exponent (between 2 and 3.5) [2,7] and grain coarsening during cyclic contact [8].…”
Section: Introductionmentioning
confidence: 99%
“…The earliest experiment to report grain coarsening in response to fatigue is by Witney et al [1], who reported on the microstructural evolution of nanocrystalline copper. Since then, other experimental works involving fatigue on nanocrystalline nickel and nickel-tungsten alloys [2], ultrafine-grained copper [3,4] and nickel-manganese alloys [5] have noted grain coarsening. The coarsening has been cited as the reason for the observed cyclic softening in nanocrystalline materials [3] and for contributing to crack initiation [5], but the mechanisms for the growth are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Rupert et al 4 have experimentally uncovered the shear-stress-driven GB migration behaviour in the aluminium film using the specimens smartly designed with stress and strain concentrators. Until now, the grain growth has been observed under various loading modes including tension 5,6 , compression 7 , nanoindentation 3,8 and cyclic deformation 9,10 .…”
mentioning
confidence: 99%